2019
DOI: 10.1007/s00442-019-04497-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of secondary forest regeneration on ground-dwelling ant communities in the Tropical Andes

Abstract: Natural regeneration of abandoned farmland provides an important opportunity to contribute to global reforestation targets, including the Bonn Challenge. Of particular importance are the montane tropics, where a long history of farming, frequently on marginal soils, has rendered many ecosystems highly degraded and hotspots of extinction risk. Ants play crucial roles in ecosystem functioning, and a key question is how time since abandonment and elevation (and inherent temperature gradients therein) affect patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Any habitat change that affects forest heterogeneity could reduce its large temperature buffering potential (Blonder et al, 2018;Jucker et al, 2020), and butterfly diversity as a whole (Montejo-Kovacevich et al, 2018). Nevertheless, microclimates have been shown to recover decades after low impact land-uses (González del Pliego et al, 2016;Mollinari et al, 2019;Senior et al, 2018), allowing for recolonization of biodiversity (Hethcoat et al, 2019). This highlights the need to protect degraded secondary forest, as these are now more abundant than primary forests in most of the tropics (Edwards et al, 2011;Senior et al, 2017).…”
Section: Conserv Atio N Implic Ationsmentioning
confidence: 99%
“…Any habitat change that affects forest heterogeneity could reduce its large temperature buffering potential (Blonder et al, 2018;Jucker et al, 2020), and butterfly diversity as a whole (Montejo-Kovacevich et al, 2018). Nevertheless, microclimates have been shown to recover decades after low impact land-uses (González del Pliego et al, 2016;Mollinari et al, 2019;Senior et al, 2018), allowing for recolonization of biodiversity (Hethcoat et al, 2019). This highlights the need to protect degraded secondary forest, as these are now more abundant than primary forests in most of the tropics (Edwards et al, 2011;Senior et al, 2017).…”
Section: Conserv Atio N Implic Ationsmentioning
confidence: 99%
“…The ubiquity of anthropogenic pressures in tropical regions is the primary threat to biodiversity, and one of the most significant challenges humanity is currently facing (Lewis et al, 2015). Hope is set on regrowing secondary forests, which may serve as habitat refugia for many species and play a central role in ecosystem functioning (Hethcoat et al, 2019). Secondary forests currently account for over half of the world's tropical forests, and their distribution is expanding as they gradually replace old-growth stands that have been clear-cut for productive use, but subsequently abandoned (Chazdon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While climatically driven elevational shifts have been documented for some invertebrate groups (e.g., moths moving up by 67 m in 40 years (Chen et al, 2009)), recent studies highlight the importance of consistent sampling methods and timing: if such methodological variance is considered, range shifts can appear to be less pronounced (Cheng et al, 2019) or driven by natural seasonality (Maicher et al, 2020). For cloud forest ant assemblages, several recent studies that consider both habitat change and elevation found that the mountain assemblages are more robust to vegetation changes than their lowland counterparts (Hethcoat et al, 2019; Mottl et al, 2019). This paints a more optimistic picture that mountain ants in these tropical environments might be perhaps also less sensitive to climatic changes.…”
Section: Discussion and Perspectivementioning
confidence: 99%